IMPLIKASI PENERAPAN MODEL PEMBELAJARAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN MENGANALISIS TEKS EKSPOSISI PADA SISWA KELAS X MIPA 7 SMA NEGERI 7 DENPASAR TAHUN PELAJARAN 2018/2019 - Ariyatni, Ni Made (LPPM IKIP PGRI Bali, 2019)
This study aims to find out and improve the ability to analyze exposition text in a systematic and detailed manner by applying the inquiry learning model to class X students. This classroom action research was carried out at Denpasar 7 Public High School located on Jl. Kaamboja No.9 Denpasar, Bali. Subjects of class X MIPA 7 Denpasar Senior High School 7 in the odd semester of school year 2018/2019, while the object of this study was a study of exposition text analysis and student responses to inquiry learning models. This research was conducted in class X MIPA 7 Denpasar Senior High School 7.          The application of inquiry learning models can improve the ability to analyze exposition text on students and the application of inquiry learning models can also improve the response of students of class X MIPA 7 in analyzing exposition texts. The implication of the application of the inquiry learning model was declared successful to improve the ability to analyze the exposition text of class X MIPA 7 Public High School 7 Denpasar academic year 2018/2019. This research has fulfilled the indicators of success determined through cycle I and cycle II.